Actual and imagined music-cued gait training for people with multiple sclerosis: a multicentre qualitative study - Barbara Seebacher; Christian Brenneis; Rainer Ehling; Florian Deisenhammer; Christian Enzinger; Birgit Helmlinger; Daniela Pinter; Isabella Hotz (BMJ Open)
Objectives To explore the experiences and acceptability of music-cued motor imagery (MCMI), music-cued gait training (MCGT), and combined MCMI and MCGT (MCMI-MCGT) in people with multiple sclerosis (pwMS). We also aimed to explore participants’ self-rated health status postintervention and gather recommendations for further programme development.Design Qualitative study alongside the double-blind randomised controlled real and imagined gait training with music-cueing (RIGMUC) multicentre trial of MCMI, MCGT and MCMI-MCGT.Setting PwMS recruited for the RIGMUC trial from Departments of Neurology at Medical Universities of Innsbruck and Graz and Clinic for Rehabilitation Muenster, Austria.Participants All 132 pwMS with mild to moderate disability randomised into the trial were included in the analysis.Methods Participants practised home-based MCMI, MCGT or MCMI-MCGT for 30 min, 4×/week, for 4 weeks. Three trained researchers conducted weekly semistructured telephone interviews during the intervention period, supporting adherence, addressing problems, sharing experiences and assessing intervention acceptability. Follow-up interviews at 4-week postintervention aimed to understand participants’ self-rated changes in walking, fatigue and overall health compared with their prestudy condition. Investigator triangulation was employed among the researchers to enhance trustworthiness and credibility.Results Using thematic analysis, we identified five themes: (1) empowerment, (2) remaining in sync, (3) interconnection between imagined and actual walking, (4) sustaining focus and (5) real-world transfer. Participants appreciated and found the imagined and actual MCGT innovative. Problems included concentration issues, early fatigue in advanced disability and difficulty synchronising with music cues. Positive changes in walking, fatigue and overall health postinterventions were reported offering valuable insights for programme development.Conclusions A participatory study to codevelop a music-cued exercise programme for pwMS seems appropriate as participants appreciated the innovation and effectiveness of both imagined and actual MCGT. Future studies should also investigate pwMS’ potential and limitations in enhancing their MCMI abilities with intensive therapist-supported practice.Trial registration number DRKS00023978.